Low-Dimensional Assemblies of Magnetic MnFe2O4Nanoparticles and Direct in Vitro Measurements of Enhanced Heating Driven by Dipolar Interactions: Implications for Magnetic Hyperthermia - Sanz, Beatriz (2020)
Magnetic fluid hyperthermia (MFH), the procedure of raising the temperature of tumor cells using magnetic nanoparticles (MNPs) as heating agents, has proven successful in treating some types of cancer. However, the low heating power generated under physiological conditions makes it necessary a high local concentration of MNPs at tumor sites. Here, we report how the in vitro heating power of magnetically soft MnFe2O4 nanoparticles can be enhanced by intracellular low-dimensional clusters through a strategy that includes: (a) the design of the MNPs to retain Néel magnetic relaxation in high-viscosity media, and (b) culturing MNP-loaded cells under magnetic fields to produce elongated intracellular agglomerates. Our direct in vitro measurements demonstrated that the specific loss power (SLP) of elongated agglomerates (SLP = 576 ± 33 W/g) induced by culturing BV2 cells in situ under a dc magnetic field was increased by a factor of 2 compared to the SLP = 305 ± 25 W/g measured in aggregates freely formed within cells. A numerical mean-field model that included dipolar interactions quantitatively reproduced the SLPs of these clusters both in phantoms and in vitro, suggesting that it captures the relevant mechanisms behind power losses under high-viscosity conditions. These results indicate that in situ assembling of MNPs into low-dimensional structures is a sound possible way to improve the heating performance in MFH.